Faktor-faktor yang Mempengaruhi Status Stunted pada Anak Usia Dua Tahun ke Bawah di Puskesmas Karya Mulia pada Tahun 2023 - Wahyudi, Dery; Fahiratunnisa, Namira Alifah; Refaldi, Muhammad Wildan; Asseggaf, Syarifah Nurul Yanti Rizki Syahab (Jurnal Biomedika dan Kesehatan, 2024)
Background Stunted (short stature), defined as a height-for-age condition less than two standard deviations below the median of the WHO child growth standards, is caused by inadequate nutritional intake during the first 1000 days of life. Various factors contribute to the stunted status in children. Therefore, this research focuses on factors that can be examined at primary healthcare facilities, such as public health centers, and their relationship with the stunted status in children. Objective To determine the relationship between birth weight, basic complete immunization, and vitamin A supplementation on the stunted status of children aged 12-23 months at Karya Mulia Public Health Center, Pontianak, in the year 2023. Methods This study employed an analytical design with a cross-sectional approach. A total of 86 research samples were selected using total sampling techniques that met the sample criteria. Bivariate analysis was conducted using the fisher’s exact test and chi-square test. Results The results indicate no significant relationship between birth weight (0.623), basic complete immunization (0.342), and vitamin A supplementation (0.602) on the stunted status of children aged 12-24 months at Karya Mulia Public Health Center in 2023, statistically with p-value > 0.05. Conclusions There is no relationship between birth weight, basic complete immunization status, and vitamin A supplementation on the stunted status of children aged 12-23 months at Karya Mulia Public Health Center.